Investigation of Corrosion Fatigue of Duplex Steel X2CrNiMoN22-5 3 Exposed to a Geothermal Environment under Different Electrochemical Conditions and Load Types. (July 2017) - Wolf, Marcus; Afanasiev, Roman; Böllinghaus, Thomas; Pfennig, Anja
Abstract: Corrosion fatigue (CF) of duplex stainless steel (DSS) X2CrNiMoN22-5-3 was investigated in in-situ geothermal conditions of the Northern German Basin (NGB). The influence of the load type on CF behavior of the alloy was examined by applying push/pull and rotating bending cyclic load to failure. The hour-glass shaped specimens with both polished and precisely turned surface finish were tested in corrosion chambers allowing for the permanent circulation of Northern German Basin electrolyte heated to 369 K. Additionally, the influence of a protective cathodic potential on the CF life expectancy was investigated by employing a potentiostat. The rotating bending cyclic load led to a higher CF life expectancy, which decreased with increasing duration of the experiment due to a higher deterioration rate of the material. The application of a cathodic potential caused a significant increase of the CF lifespan from 4.7 x 10 5 (open-circuit potential (OCP)) to 10 7 cycles (preset threshold cycle number) for the potential range from USHE = – 450 to – 900 mV. Microstructural analysis of the CF damage revealed horizontal grain attack within corrosion pit cavities, multiple fatigue cracks and preferable deterioration of the austenitic phase.